Together but Alone: Exploring the Predictors of Phubbing Behaviour in Married Individuals - Harshita Jain; Ayushi Tyagi (International Journal of Indian Psychȯlogy, 2024)
Marital relationship holds profound significance, serving as a cornerstone for emotional support, and personal growth. Moreover, the commitment and satisfaction inherent in marriage fosters a sense of security and belonging. Personality traits on the other hand play a crucial role in the success and dynamics of a marriage shaping the interactions, communications, and overall satisfaction. The present study aims at exploring the predicting factors that contributes to phubbing behavior in married individuals. The study sample consisted of 100 married individuals (25-45 years). Significant results of correlation and regression indicated that relationship commitment, relationship satisfaction and personality traits (neuroticism and conscientiousness) have a major role in predicting phubbing behavior of a married individual. This study can provide an insight into relationship dynamics.